Marx and Sen on incentives and justice: Implications for innovation and development. (October 2016) - Papaioannou, Theo
The most crucial obstacle to equitable innovation and development is the tension between profit incentives and social justice. In the egalitarian tradition of social and political thought, there have been a number of theorists preoccupied with this tension. Among them Marx and Sen stand out as the most influential figures. This article evaluates their approaches and examines implications for technological innovation and economic development. The argument is that Marx's needs-based approach is relational and therefore provides a radical resolution to the incentives–justice tension. By contrast, Sen's approach is informational and therefore provides a policy solution to this tension. Both approaches imply that innovation and development can become more equitable through public action. However, in the case of Marx, public action assumes conflict between social classes; it aims at changing capitalist social relations and eliminating unjust exploitation. In the case of Sen, public action assumes consent between individuals; it aims at reforming public policy and eliminating capability deprivation.